FENOMENA ANOMALI MUSIMAN INDEKS HARGA SAHAM DI INDONESIA - G. A. Sri Oktaryani; Iwan Kusuma Negara; Weni Retnowati; Iwan Kusmayadi (Master of Management, Mataram University, 2021)
This Research aims to obtain empirical evidence about the existence of anomaly seasonal effects on market returns on a daily and monthly basis on the IHSG and the LQ-45 Index in Indonesia throughout January 2015 untill September 2020. The diversity of arguments and research results regarding the phenomenon of seasonal anomalies in stock returns derived from previous studies make this phenomenon interesting to study. We analyze daily stock returns by using the Kruskal Wallis test, while the average monthly return is analyzed using the one-way Anova. The findings show that the phenomenon of stock anomaly returns according to the daily pattern of the week (day of the week effect) and the monthly pattern (month of the year effect) on IHSG and the LQ-45 Index are not proven within the range research from January 2015 to September 2020. The results of stock price forecasting provide benefits in supporting investors to develop their investment strategies. Futhermore, this information is also important to choose and determine which stocks should be bought and sold. In addition to investors, this information is also useful for management to monitor the pattern of stock price movements, so that they can plan, formulate strategies and take anticipatory steps based on possible threats that could arise.Keywords :Anomaly Seasonal Effect, day of the week effect, month of the year effect, market Return